Socio-Religious determinants of early Chinese culture - Kierzkowski, Karol (Studia Ecologiae et Bioethicae, 2014)
The claim that all living creatures constitute a wholeness in the world of nature is a primary thought of Chinese philosophy. It links both cosmological and anthropological motifs. Living creatures are interconnected and interdependent. The world of nature is tao. Tao is wholeness. The world of nature is in constant flux set by progressive cycles in which individual changes take place. When the world of nature remains stable, it reaches equilibrium. Life can develop in a harmonious way. Chinese anthropology treats the human as a microcosm of the world of nature. Man is an intermediary between Heaven and Earth and a descendant of the interpolating cosmic and earthly powers. An ideogram, found in China, presents the human figure as a tree rooted in the Earth, with hands outstretched like branches towards Heaven, deriving power from both above and below.